EVALUATION OF INFLUENCE OF DISPLAY OF INSTRUCTIONAL RESOURCES ON CHILDREN’S PERFORMANCE IN EARLY LITERACY IN PUBLIC PRE-SCHOOLS IN KANDUYI SUB-COUNTY, KENYA - Kimalel, Betty Chepkoech (IJRDO - Journal of Social Science and Humanities Research, 2023)
Availability and utilization of instructional resources play an important role in the attainment of educational goals, objectives and learners’ performance. In this study, the researcher argues that many learners are still not proficient in early literacy skills despite going through pre-school education. The factors associated with the teaching and learning of early literacy skills may have been addressed but influence of instructional resources continues to be a concern. This study focused on the influence of display of instructional resources on children’s performance in literacy. The study was framed on the constructivism theory propounded by Jean Piaget in 1896-1980. The study adopted a descriptive survey design and targeted 90 public pre-schools comprising of 5460 pre-school learners and 180 pre-school teachers. A simple random sampling technique was used in selecting the pre-schools and the sample size for teachers and learners for the study was arrived at using Krejcie and Morgan (1970) formula. Through these methods, 27 pre-schools, 359 learners and 123 pre-school teachers were selected for the study. Data was collected using questionnaires and a literacy skill test administered to the learners. Questionnaires were administered to pre-school teachers to seek information on pre-school teachers’ training skills and use of instructional resources. Content validity of the instruments was determined by employing the expertise of my supervisors and lecturers in the Department of Education while reliability was determined through split-half technique. Data was analyzed using descriptive and inferential statistics such as means, percentages, frequencies and Pearson Correlation analysis. The findings were presented in tables, pie charts and bar graphs. The study found that there was a positive correlation between display of instructional resources and learners’ achievement in writing skills (r = .646; p = .000) and reading skills (r = .780; p = .000). The study concluded that instructional resources play a significant role in imparting of reading and writing skills to the pre-school learners. The study recommended that there is need for provision of audio and audio-visual materials to pre-schools since these materials are known to positively affect the acquisition of writing and reading skills among pre-school learners. It also recommends that the government of Kenya through the Ministry of Education ensure that pre-schools acquire instructional resources equitably distributed in the various pre-schools across the country to facilitate timely implementation of the curriculum especially in reading and writing skills for good educational foundation of the learners.